Analysis of Distribution Patterns in Mapping Cirebon Internet Service Facilities Using NNA Algorithm Based on Geographic Information Systems - Chairun Nas; Nursaka Putra; Ilwan Syafrinal (Universitas Islam Kuantan Singingi, 2021)
Cirebon city moves continually to become Smart City by making technology to public service. One form of technology to public service to is by providing internet facilities for public or for community. Currently there are several internet facility services for public, but these services are only available at certain location points and are not spread evenly. Apart from that, the government has difficulty in determining the right location points to serve as public internet service facilities. The purpose of this research is to analyze the pattern of distribution of internet facilities location points so that they can be mapped digitally using Geographic Information Systems. In this research, the data used were 49 object data points for location of internet facilities in Cirebon. Furthermore, the data will be analyzed using the Nearest Neighbor Analysis (NNA) method to determine the distribution pattern of internet facility location points. Based on the resulting distribution pattern, it can be implemented into digital mapping using Geographic Information Systems. So the Geographic Information System can help the government in making decisions, and for the public to find out the location points of internet facilities in Cirebon.